Pengembangan Jaringan Komputer Dan Manajemen Bandwidth Dengan Menerapkan Metode Per Connection Queue ( Studi Kasus : Pengadilan Negeri Salatiga ) - Triya Setiawan, Ananda, Muhammad Kusban, S.T, M.T (2015)
Abstract Computer network in the Pengadilan Negeri Salatiga actually doesn't require large bandwidth if only to perform browsing data and information, but will appear various kinds of problems such as the slow internet access or pull attractive bandwidth if client access to the internet a lot. Besides, the security hotspot area is very important because in order to prevent or minimize attacks hacking hotspot impacting the State agencies for poor. So as to solve the problems, given solution is the use of router and security hotspot area use the MAC Address because in Pengadilan Negeri Salatiga is only used for private agencies. Research method used are observation, literature and interview. Equipment used are by mozilla firefox, winbox 6.24 version, net monitoring for employees pro as the supporting software and MikroTik RB450G as hardware. Upgrading and Management bandwidht using mikrotik RB450G produce limit bandwidth LAN Lt.1 and LAN Lt.2 by 25.6kb/s, for Wi-Fi by 9.85kb/s when internet traffics crowded and produce limit bandwidth LAN Lt.1 and LAN Lt.2 by 256kb/s, for Wi-Fi by 128kb/s when internet traffics deserted. Bandwidth per client are not used will be automatically used by other clients. Make it easier for the administrator of the network in configuration if there are additional client. To increase the safety of the hacking hotspot and could help speed up a data transmission for supporting speed GigaBytes/s. Keyword : MikroTik, Bandwidth, Hotspot, MAC Address, Subnetting